Digital Parenting Can Reduce Problematic Internet Use In Early Childhood - Lutfi Hidayati Fauziah; Lukman Hakim; Miftahul Izza Rofiqoh; Umbu Hendro Nasrani Blegur (LPPM Universitas 17 Agustus 1945 Samarinda, 2026)
This study aimed to examine the effect of digital parenting on problematic internet use among early childhood children. The participants were 200 mothers of children aged 3–5 years enrolled in early childhood education institutions in Singosari District, Malang Regency. Participants were selected using a purposive sampling technique. Data were collected using the Internet Parenting Scale (IPS), consisting of 10 items (α = 0.903), and the Problematic Internet Use Questionnaire (PIUQ), consisting of 18 items (α = 0.944). Data were analyzed using simple linear regression. The results revealed that digital parenting had a significant negative effect on problematic internet use among early childhood children (β = -0.772, R² = 0.596, F = 291.710, p < .001). Digital parenting accounted for 59.6% of the variance in problematic internet use, indicating that higher levels of parental guidance, monitoring, and involvement in children's digital activities were associated with lower levels of problematic internet use. These findings suggest that effective digital parenting serves as an important protective factor in preventing problematic internet use during early childhood. The study highlights the importance of strengthening parents’ digital parenting competencies through supervision, guidance, and active engagement in children's technology use to promote healthier digital behaviors from an early age.